Humans and horses in the Late Roman Period - Late Migration Period (3rd-7th centuries) in Lithuania: origins and social context - Kurila, Laurynas; Piličiauskienė, Giedrė (Archaeologia Lituana, 2025)
This paper presents a study analysing the mobility and possible immigration of humans and horses in Lithuania in the Late Roman Period – Migration Period (3rd–7th centuries AD), based on 87Sr/86Sr stable isotopes analysis. During the study, we carried out strontium analysis of 40 human teeth from 11 burial sites and 13 horses from six burial sites. In addition, to reconstruct bioavailable 87Sr/86Sr ranges, we analysed 87Sr/86Sr of 41 animals from 15 prehistoric and historic sites. A human sample was collected to evaluate the presumed immigration directions and mobility of both sexes, different social groups, and in different regions of Lithuania. Stable isotope analysis, radiocarbon dating, biometric measurements, and other studies have provided new insights into the origins, mobility, and other aspects of lifestyle and horse breeding in the mid-1st millennium AD, and have also drawn prospects for future research on these topics.
Keywords: 87Sr/86Sr stable isotope analysis; migration; mobility; Late Roman Period; Migration Period; Southeastern Baltic; humans; horses